2005
DOI: 10.1007/s00441-004-1053-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of osteoclastogenesis in porcine bone marrow cultures by quercetin and rutin

Abstract: Flavonols, in contrast to soybean isoflavones, are the most abundant phytoestrogens in western diets, being present in onions, beans, fruits, red wine, and tea. They may protect against atherosclerosis, inhibit certain cancer cell types, and reduce bone resorption. The most widely distributed flavonol is quercetin, which occurs mainly as its glycoside, rutin, but data are very scarce regarding the precise mechanism of action of these compounds on bone-resorbing cells at concentrations similar to those detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 72 publications
(80 reference statements)
0
35
1
1
Order By: Relevance
“…Rutin did not show cytotoxicity to either bone marrow cells or BMM under these conditions (Data not shown). Rassi et al (2005) showed that nanomolar concentration of rutin reduced 1,25-dihydroxyvitamin D3-induced bone resorption in porcine bone marrow cells. Rutin could be more sensitive in inhibiting bone resorption activity than in inhibiting osteoclast formation, although we did not measure the effect of rutin on functional activity of osteoclast.…”
Section: Discussionmentioning
confidence: 98%
“…Rutin did not show cytotoxicity to either bone marrow cells or BMM under these conditions (Data not shown). Rassi et al (2005) showed that nanomolar concentration of rutin reduced 1,25-dihydroxyvitamin D3-induced bone resorption in porcine bone marrow cells. Rutin could be more sensitive in inhibiting bone resorption activity than in inhibiting osteoclast formation, although we did not measure the effect of rutin on functional activity of osteoclast.…”
Section: Discussionmentioning
confidence: 98%
“…7 macrophages treated with receptor activator of NF-kB (RANK) ligand, as well as human peripheral blood mononuclear cells differentiated with macrophage colony-stimulating factor and RANK ligand Woo et al 2004). Moreover, Rassi et al (2005) have recently demonstrated in a porcine bone-marrow model that even low nanomolar concentrations of quercetin or rutin significantly inhibit osteoclast formation and activity similar to 17b oestradiol. Kaempferol (1-6 mM), another flavonol found in alcoholic beverages, also induces apoptosis and inhibits bone resorption activity in primary rabbit osteoclasts even at concentrates of less than 1 mm (Wattel et al 2003).…”
Section: Rutin Quercetin and Kaempferolmentioning
confidence: 99%
“…These in vivo effects suggest that either rutin, or its active metabolites quercetin and isorhamnetin, may exert modulatory effects on bone cells. Indeed, results from in vitro studies (Wattel et al 2003Woo et al 2004; Rassi et al 2005) suggest that both rutin and quercetin may directly affect bone cells, particularly osteoclasts. Quercetin has been reported to induce apoptosis in primary rabbit or porcine osteoclasts (Wattel et al 2003;Rassi et al 2005).…”
Section: Rutin Quercetin and Kaempferolmentioning
confidence: 99%
See 1 more Smart Citation
“…3) have also been shown to modulate the activity of bone cells in vitro and in vivo. During an 11 d incubation, both rutin and quercetin (10 nM) significantly inhibited the formation of osteoclasts in porcine bone marrow cells treated with 1,25-dihydroxyvitamin D 3 (10 nM) 33 . In the same study, a 48 h treatment of 11 d old osteoclast cells with rutin or quercetin (10 nM) was also shown to significantly reduce bone resorption.…”
Section: Flavonoidsmentioning
confidence: 99%